Application of a bacteriophage cocktail to reduce Salmonella Typhimurium U288 contamination on pig skin - Hooton, Steven P.T.; Atterbury, Robert J.; Connerton, Ian F. (Elsevier, 2011)
Multidrug-resistant Salmonella Typhimurium U288 is a significant pathogen of pigs, accounting for over half of all outbreaks on UK pig production premises. The potential of this serovar, and other salmonellae, to enter the food chain during the slaughtering process requires that efforts be made to reduce the prevalence of these bacteria at both the pre- and post-harvest stages of production. A bacteriophage cocktail (PC1) capable of lysing various Salmonella enterica serovars was designed using the broad host-range phage Felix 01, and three phages isolated from sewage. PC1 applied to pig skin experimentally-contaminated with U288 achieved significant reductions (P < 0.05) in Salmonella counts when stored at 4 °C over 96 h. Reductions of > 1 log10 unit were observed when the ratio of phage applied was in excess of the bacterial concentration. The treatment was found to be effective at a multiplicity of infection (MOI) of 10 or above, with no significant reductions taking place when the MOI was less than 10. Under these conditions U288 counts of log10 4.1–4.3 CFU were reduced to undetectable levels following the application of PC1 to pig skin (> 99% reduction). These data suggest phage cocktails could be employed post-slaughter as a means to reduce Salmonella contamination of pig carcasses.